Modifier, magnesium oxychloride composite material and preparation method and application thereof

Through the combination of modifier and composite materials, the problems of slow solidification, poor heat dissipation and poor weather resistance at low temperatures are solved, and the rapid solidification at low temperatures and stable stability at high temperatures are achieved. Molds improve production efficiency and mold stability.

CN116119975BActive Publication Date: 2024-12-17王再根
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310039676.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-12
Publication Date
2024-12-17
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

The existing magnesium oxychloride ceramic molds are slow to solidify, have poor heat dissipation and poor weather resistance at low temperatures, resulting in insufficient strength and easy cracking of molds, and react quickly at high temperatures, resulting in great physical heat influence and unstable products.

Method used

The modifier is composed of phosphoric acid, hydrochloric acid, tributyl phosphate, tridecafluorosilane, graphene and hydroxypropyl methylcellulose. The water resistance and heat dissipation properties of magnesium oxychloride materials are improved by adding modifiers, and Magnesium sulfate and bamboo powder are added to the magnesium oxychloride composite material to inhibit expansion and increase strength.

Benefits of technology

The modifier causes the magnesium oxychloride material to solidify rapidly at low temperatures, and the surface of the formed product is bright and weather-resistant. It is not easy to crack when the temperature is high, and has good heat dissipation performance, which improves production efficiency and mold stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a modifier, a magnesium oxychloride composite material, and a preparation method and application thereof, which belong to the field of mold materials. The modifier is composed of the following raw materials by mass fraction: 30-70% phosphoric acid, 1-3% hydrochloric acid, 1-2.2% tributyl phosphate, 1-3% tridecafluorosilane, 0.1-0.5% graphene, 0.01-0.1% hydroxypropyl methylcellulose, and the balance is deionized water. The magnesium oxychloride composite material is composed of the following materials by mass fraction: 45-55% magnesium oxide, 35-45% magnesium chloride, 3-13% magnesium sulfate, 3-8% bamboo powder, 0.15-0.5% polypropylene fiber, 0.1-0.5% water reducer, and 0.3-1.5% modifier. The modifier of the present invention can improve the poor weather resistance and poor heat dissipation of magnesium oxychloride materials; when the magnesium oxychloride composite material of the present invention is used for the production of blister molds, the product can maintain a stable state for a long time without cracking or anti-halogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of mold materials, and specifically relates to a modifier. In addition, the invention also relates to a magnesium oxychloride composite material and a preparation method and application thereof. Background Art

[0002] Existing plastic blister molds are mainly divided into plaster molds, copper molds, aluminum molds, resin molds, ceramic molds, etc. Plaster molds have low strength and are not resistant to high temperatures; electroplated copper molds take a long time and are expensive; aluminum molds are mainly engraved, although the quality is good but the price is expensive; resin molds shrink a lot and are expensive.

[0003] Although the price of ceramic mold materials made of magnesium oxychloride is low, they still have the following shortcomings:

[0004] Magnesium oxychloride materials do not solidify or solidify slowly in areas with low temperatures, which greatly prolongs the production time, causing the mold to fail to reach the required strength, and then causing the mold to crack when it is put on the machine for production. The existing magnesia ceramic mold has slow heat dissipation, which prolongs the production time and the delivery rate is lower than other molds; and the magnesia ceramic mold has poor weather resistance, and the mold will crack, deform and reverse halogen after being made for a period of time; when the temperature is high, magnesia reacts quickly and the physical heat of the reaction is high, which makes it difficult to produce. The existing method is to add miscellaneous powder to reduce the activity of magnesium oxide, or reduce the magnesium chloride porosity, but the strength of the mold will be greatly reduced. Summary of the invention

[0005] Based on the above background problems, the present invention aims to provide a modifier that can improve the problems of magnesium oxychloride materials such as poor water and weather resistance, poor heat dissipation performance, and susceptibility to physical heat. Another object of the present invention is to provide a magnesium oxychloride composite material that can maintain a stable state for a long time without cracking or halogen reversal when used in the production of blister molds.

[0006] To achieve the above objectives, on the one hand, the technical solution provided by the embodiments of the present invention is:

[0007] The modifier is composed of the following raw materials in mass fractions:

[0008] Phosphoric acid 30-70%, hydrochloric acid 1-3%, tributyl phosphate 1-2.2%, tridecafluorosilane 1-3%, graphene 0.1-0.5%, hydroxypropyl methylcellulose 0.01-0.1%, and the balance is deionized water.

[0009] In one embodiment, the modifier is composed of the following raw materials by mass fraction:

[0010] Phosphoric acid 60-70%, hydrochloric acid 1-1.5%, tributyl phosphate 2-2.2%, tridecafluorosilane 1-1.5%, graphene 0.1-0.3%, hydroxypropyl methylcellulose 0.05-0.08%, and the balance is deionized water.

[0011] The addition of phosphoric acid to the modifier of the present invention can well solve the problem of water resistance and weather resistance; the role of hydrochloric acid is to supplement chloride ions. It is conventionally believed in the art that excess chloride ions will easily lead to halogen reversal, but this is not the case. The existing magnesium chloride will be carbonized due to dehydrogenation after being dissolved, so that the magnesium oxychloride material cannot produce a good chemical reaction. The present invention can make the magnesium oxychloride react more completely and quickly form crystals by appropriately supplementing hydrogen chloride, so that the surface of the product is as bright as a mirror.

[0012] The tributyl phosphate in the modifier of the present invention can be used to eliminate bubbles, thereby increasing the density of the product and improving the water resistance; tridecafluorosilane is combined with graphene, wherein the graphene is dispersed in tridecafluorosilane and forms a fluorosilicone resin after hydrolysis, which can increase the strength and hydrophobicity of the product and make the product have better heat dissipation performance; hydroxypropyl methylcellulose has fast film formation, which can increase the viscosity of the magnesium oxychloride material and form a thin film on the surface of the product, so that the product is not easy to absorb moisture and dehalogenate, and can also reduce the physical reaction heat when the temperature is high.

[0013] On the other hand, an embodiment of the present invention provides a magnesium oxychloride composite material, comprising the modifier.

[0014] In one embodiment, the amount of the modifier added is 0.3-1.5 wt %.

[0015] In one embodiment, the magnesium oxychloride composite material is composed of the following materials by mass fraction:

[0016] Magnesium oxide 45-55%, magnesium chloride 35-45%, magnesium sulfate 3-13%, bamboo powder 3-8%, polypropylene fiber 0.15-0.5%, water reducing agent 0.1-0.5%, modifier 0.3-1.5%.

[0017] In one embodiment, the magnesium oxychloride composite material is composed of the following materials by mass fraction:

[0018] Magnesium oxide 48-50%, magnesium chloride 35-40%, magnesium sulfate 6-12%, bamboo powder 4-5%, polypropylene fiber 0.2-0.3%, water reducing agent 0.1-0.3%, modifier 0.3-0.5%.

[0019] Magnesium oxychloride materials will expand to varying degrees after solidification, and the addition of magnesium sulfate in the present invention can effectively inhibit the expansion of the magnesium oxychloride material. When used for mold making, the mold can be maintained at a normal size, thereby meeting the size requirements of the blister mold.

[0020] The magnesium oxychloride material of the invention is added with bamboo powder and polypropylene fiber. When used for mold manufacturing, the strength of the mold can be increased while the weight of the mold is reduced, thereby preventing the mold from breaking during product manufacturing.

[0021] In a third aspect, an embodiment of the present invention provides a method for preparing a magnesium oxychloride composite material, comprising the following steps:

[0022] Adding a water reducing agent into magnesium oxide powder and mixing evenly to obtain a magnesium oxide mixture;

[0023] The bamboo powder and polypropylene fiber are mixed evenly, and then magnesium chloride solution is added, and then magnesium sulfate and magnesium chloride flakes are added and stirred evenly to obtain a dry mix;

[0024] The dry mixture is added with water and stirred, then the modifier is added and stirred evenly, and finally the magnesium oxide mixture is added and stirred evenly to obtain a slurry.

[0025] In one embodiment, the magnesium chloride solution has a Baume degree of 25-30°Bé.

[0026] In one embodiment, the mass ratio of the dry mix to water is 2-3:1.

[0027] In a fourth aspect, an embodiment of the present invention provides an application of a magnesium oxychloride composite material in a blister mold.

[0028] Compared with the prior art, the embodiments of the present invention have at least the following effects:

[0029] 1. The modifier of the present invention solves the problems of water resistance and weather resistance through phosphoric acid, makes the surface of the product as bright as a mirror through hydrochloric acid, and increases the density of the product through tributyl phosphate to improve the water resistance; the product has better heat dissipation performance through the combination of tridecafluorosilane and graphene; the film-forming property of hydroxypropyl methylcellulose makes the product less likely to absorb moisture and reverse halogen, and the physical reaction heat can also be reduced when the temperature is high. That is, the modifier of the present invention can improve the problems of poor water resistance and weather resistance, poor heat dissipation performance, and easy influence by physical heat of magnesium oxychloride materials.

[0030] 2. The magnesium oxychloride composite material of the present invention can solidify quickly under low temperature conditions, greatly shortening the molding time; the formed product has a bright surface and strong weather resistance; it is not easily affected by physical heat when the temperature is high, and the formed product can maintain a stable state for a long time without cracking or anti-halogen; the formed mold also has the advantage of fast heat dissipation when used to make finished products, thereby greatly improving production efficiency. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In order to solve the problems of slow solidification, poor heat dissipation and poor weather resistance of the existing magnesium oxychloride materials at low temperatures, the embodiment of the present invention provides a modifier, which solves the water and weather resistance problems by phosphoric acid, makes the surface of the product as bright as a mirror by hydrochloric acid, and increases the density of the product by tributyl phosphate to improve the water resistance; the product has better heat dissipation performance by combining tridecafluorosilane and graphene; the film-forming property of hydroxypropyl methylcellulose makes the product less likely to absorb moisture and reverse halogen, and the physical reaction heat can also be reduced when the temperature is high. That is, the modifier of the present invention can improve the problems of poor water and weather resistance, poor heat dissipation and susceptibility to physical heat of magnesium oxychloride materials.

[0033] Next, the technical solution of the present invention will be described through specific embodiments.

[0034] Example 1

[0035] The modifier is composed of the following raw materials in mass fractions:

[0036] Phosphoric acid 30%, hydrochloric acid 1%, tributyl phosphate 2%, tridecafluorosilane 1%, graphene 0.1%, hydroxypropyl methylcellulose 0.01%, deionized water 65.89%.

[0037] The preparation method of the modifier comprises the following steps:

[0038] (1) Pour phosphoric acid into a container, add some graphene and slowly stir evenly, then add tributyl phosphate and hydrochloric acid and continue stirring, and after stirring evenly, add deionized water;

[0039] Add the remaining graphene to tridecafluorosilane and stir evenly, then add it to the above container and mix, stir for 3-5 minutes to obtain a mixed solution, and set aside;

[0040] (2) Dissolve hydroxypropyl methylcellulose in water to obtain a colloidal solution for later use.

[0041] Example 2

[0042] The modifier is composed of the following raw materials in mass fractions:

[0043] Phosphoric acid 45%, hydrochloric acid 1%, tributyl phosphate 2%, tridecafluorosilane 1%, graphene 0.1%, hydroxypropyl methylcellulose 0.01%, deionized water 50.89%.

[0044] The preparation method of the modifier of this embodiment is the same as that of embodiment 1.

[0045] Example 3

[0046] The modifier is composed of the following raw materials in mass fractions:

[0047] Phosphoric acid 60%, hydrochloric acid 3%, tributyl phosphate 1%, tridecafluorosilane 3%, graphene 0.5%, hydroxypropyl methylcellulose 0.1%, deionized water 32.4%.

[0048] The preparation method of the modifier of this embodiment is the same as that of embodiment 1.

[0049] Example 4

[0050] The modifier is composed of the following raw materials in mass fractions:

[0051] Phosphoric acid 65%, hydrochloric acid 1%, tributyl phosphate 2%, tridecafluorosilane 1.2%, graphene 0.3%, hydroxypropyl methylcellulose 0.05%, deionized water 30.45%.

[0052] The preparation method of the modifier of this embodiment is the same as that of embodiment 1.

[0053] Example 5

[0054] The modifier is composed of the following raw materials in mass fractions:

[0055] Phosphoric acid 70%, hydrochloric acid 2%, tributyl phosphate 2.2%, tridecafluorosilane 1.5%, graphene 0.4%, hydroxypropyl methylcellulose 0.08%, deionized water 23.82%.

[0056] The preparation method of the modifier of this embodiment is the same as that of embodiment 1.

[0057] Example 6

[0058] Magnesium oxychloride composite material, composed of the following raw materials in mass fraction:

[0059] 45% magnesium oxide, 45% magnesium chloride, 5.25% magnesium sulfate, 3% bamboo powder, 0.15% polypropylene fiber, 0.1% water reducing agent, and 1.5% modifier in Example 4.

[0060] The preparation method of the magnesium oxychloride composite material comprises the following steps:

[0061] (1) adding a water reducing agent to magnesium oxide powder and mixing the mixture uniformly to obtain a magnesium oxide mixture;

[0062] (2) After bamboo powder and polypropylene fiber are uniformly mixed, a magnesium chloride solution is added, wherein the Baume degree of the magnesium chloride solution is 30° Bé, and the solution is prepared by adding anhydrous magnesium chloride into deionized water and stirring uniformly;

[0063] The mixed solution in step (1) of Example 1 is added to the magnesium chloride solution and stirred evenly, and then magnesium sulfate and the remaining magnesium chloride flakes are added and stirred evenly to obtain a dry mix;

[0064] (3) Add water to the dry blend and stir, the mass ratio of the dry blend to water is 3:1, then add the magnesium oxide mixture and stir evenly, and finally add the hydroxypropyl methylcellulose colloidal liquid in step (2) of Example 1 and stir evenly.

[0065] Example 7

[0066] Magnesium oxychloride composite material, composed of the following raw materials in mass fraction:

[0067] 48% magnesium oxide, 38.33% magnesium chloride, 8% magnesium sulfate, 5% bamboo powder, 0.2% polypropylene fiber, 0.12% water reducing agent, and 0.35% modifier in Example 4.

[0068] The preparation method of the magnesium oxychloride composite material comprises the following steps:

[0069] (1) adding a water reducing agent to magnesium oxide powder and mixing the mixture uniformly to obtain a magnesium oxide mixture;

[0070] (2) After bamboo powder and polypropylene fiber are uniformly mixed, a magnesium chloride solution is added, wherein the Baume degree of the magnesium chloride solution is 26°Bé, and the solution is prepared by adding anhydrous magnesium chloride into deionized water and stirring uniformly;

[0071] The mixed solution in step (1) of Example 1 is added to the magnesium chloride solution and stirred evenly, and then magnesium sulfate and the remaining magnesium chloride flakes are added and stirred evenly to obtain a dry mix;

[0072] (3) Add water to the dry blend and stir, the mass ratio of the dry blend to water is 2:1, then add the magnesium oxide mixture and stir evenly, and finally add the hydroxypropyl methylcellulose colloidal liquid in step (2) of Example 1 and stir evenly.

[0073] Example 8

[0074] Magnesium oxychloride composite material, composed of the following raw materials in mass fraction:

[0075] 48% magnesium oxide, 35.1% magnesium chloride, 12% magnesium sulfate, 4% bamboo powder, 0.25% polypropylene fiber, 0.3% water reducing agent, and 0.35% modifier in Example 4.

[0076] The preparation method of the magnesium oxychloride composite material in this embodiment is the same as that in Example 7.

[0077] Example 9

[0078] Magnesium oxychloride composite material, composed of the following raw materials in mass fraction:

[0079] 49% magnesium oxide, 39.75% magnesium chloride, 6% magnesium sulfate, 4.5% bamboo powder, 0.25% polypropylene fiber, 0.15% water reducing agent, and 0.35% modifier in Example 4.

[0080] The preparation method of the magnesium oxychloride composite material in this embodiment is the same as that in Example 7.

[0081] Example 10

[0082] Magnesium oxychloride composite material, composed of the following raw materials in mass fraction:

[0083] 55% magnesium oxide, 35% magnesium chloride, 3% magnesium sulfate, 5% bamboo powder, 0.5% polypropylene fiber, 0.5% water reducing agent, and 1% modifier in Example 4.

[0084] The preparation method of the magnesium oxychloride composite material in this embodiment is the same as that in Example 7.

[0085] The magnesium oxychloride composite material in Example 7 of the present invention can reach initial setting within 3 hours under the condition of 5°C, the strength can reach 85% after 24 hours, and the product can be made after 40 hours; when the temperature is 0°C, it can reach initial setting within 4 hours, the strength can reach 80% after 24 hours, and the product can be made after 48 hours. That is, the magnesium oxychloride composite material of the present invention can be quickly solidified under low temperature conditions, greatly shortening the molding time, and the formed mold will not crack after long-term use.

[0086] It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept of the present invention, and these modifications and improvements all fall within the protection scope of the present invention.

Claims

1. A magnesium oxychloride composite material, characterized in that: The invention comprises a modifier, which is composed of the following raw materials in mass fractions: 60-70% phosphoric acid, 1-1.5% hydrochloric acid, 2-2.2% tributyl phosphate, 1-1.5% tridecafluorosilane, 0.1-0.3% graphene, 0.05-0.08% hydroxypropyl methylcellulose, and the balance is deionized water; the addition amount of the modifier is 0.3-1.5wt%; the magnesium oxychloride composite material is composed of the following materials in mass fractions: Magnesium oxide 45-55%, magnesium chloride 35-45%, magnesium sulfate 3-13%, bamboo powder 3-8%, polypropylene fiber 0.15-0.5%, water reducer 0.1-0.5%, modifier 0.3-1.5%; The preparation method of the magnesium oxychloride composite material comprises the following steps: Adding a water reducing agent into magnesium oxide powder and mixing evenly to obtain a magnesium oxide mixture; The bamboo powder and polypropylene fiber are mixed evenly, and then magnesium chloride solution is added, and then magnesium sulfate and magnesium chloride flakes are added and stirred evenly to obtain a dry mix; Add water to the dry mix and stir, then add the modifier and stir evenly, and finally add the magnesium oxide mixture and stir evenly to obtain a slurry; The Baume degree of the magnesium chloride solution is 25-30°Bé.

2. The magnesium oxychloride composite material according to claim 1, characterized in that It is composed of the following materials by mass: Magnesium oxide 48-50%, magnesium chloride 35-40%, magnesium sulfate 6-12%, bamboo powder 4-5%, polypropylene fiber 0.2-0.3%, water reducing agent 0.1-0.3%, modifier 0.3-0.5%.

3. The magnesium oxychloride composite material according to claim 1, characterized in that The mass ratio of the dry mix to water is 2-3:

1.

4. Application of the magnesium oxychloride composite material as claimed in claim 1 in a blister mould.